2022
DOI: 10.1021/acs.chemmater.2c03045
|View full text |Cite
|
Sign up to set email alerts
|

Broadening Phosphor-Converted Light-Emitting Diode Emission: Controlling Disorder

Abstract: Near-infrared (NIR) phosphor-converted lightemitting diodes (pc-LEDs) are a highly efficient perspective NIR light source, with application hindered by a narrow emission band. In this work, we broaden the emission of a new series of NIR phosphors by controlling crystal structure disorder through cation cosubstitution. By substituting Ga 3+ with (Al 0.68 In 0.32 ) 3+ , we create a Ga 2−x (Al 0.68 In 0.32 ) x O 3 :Cr 3+ phosphor series in which the average crystal size is maintained, while cation disorder varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The spectral broadening is mainly related to the enhancement of electron–lattice coupling caused by a slight but non-negligible local structural distortion when the smaller Cr 3+ ions substitute the larger Sc 3+ or In 3+ ions. 48 The optimal Cr 3+ doping concentration is x = 0.06 based on the emission intensity, beyond which the concentration quenching effect will happen.…”
Section: Resultsmentioning
confidence: 99%
“…The spectral broadening is mainly related to the enhancement of electron–lattice coupling caused by a slight but non-negligible local structural distortion when the smaller Cr 3+ ions substitute the larger Sc 3+ or In 3+ ions. 48 The optimal Cr 3+ doping concentration is x = 0.06 based on the emission intensity, beyond which the concentration quenching effect will happen.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the elemental disorder existing in the (Ca 1− x Li x )(Mg 1− x Sc x )Si 2 O 6 ( x ≠ 0 and 1) solid solution, Cr 3+ ions tend to emit photons in a wider energy distribution. Chang et al suggested a parameter ( σ ) to quantify the disorder degree in a solid-solution system, using the following equation: 24 where N is the total number of elements, x i is the radius of particular elements i , and is the average radius of the system. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3c, the peaks at 713, 748, and 895 nm are clearly distinguishable, and the narrow line at 713 is the R line assigned to the 2 E→ 4 A 2g transition of the Cr 3+ ions. [15] The peaks at 748 and 895 nm are attributed to the two different 4 T 2g → 4 A 2g transitions of the Cr 3+ ions, which implies that there are three emission centers in the sample. Time-resolved photoluminescence spectra were measured at 7 K and are plotted in Figure 3d to further study the luminescence centers.…”
Section: Photoluminescence Properties Of Magbo:005cr 3+mentioning
confidence: 98%